International humanitarian law - Crawford, Emily (Writer on international law); Pert, Alison (Cambridge: Cambridge University Press, 2024)
"Now in its third edition, this textbook provides an accessible and up-to-date examination of international humanitarian law, with relevant cases, examples, and discussion questions. It offers students and teachers a comprehensive and logical discussion and analysis of the law, and the developing trends in theory and practice of the law"--
Historical development of international humanitarian law -- The contemporary legal basis of international humanitarian law and its fundamental principles -- Types of armed conflicts -- Individual status in armed conflict : combatants, non-combatants, direct participation in hostilities, prisoners of war and detention in non-international armed conflict -- Protection of the wounded, sick, and shipwrecked -- The protection of civilians and the law of occupation -- Targeting -- Means and methods of warfare -- The interaction between iInternational humanitarian law and international human rights law -- Implementation, enforcement, and accountability.
Includes bibliographical references and index.
SELS
Karim
Keywords: Humanitarian law; Humanitarian law -- International cooperation; International law and human rights